Hydrophilic Magnetochromatic Nanoparticles with Controllable Sizes and Super-high Magnetization for Visualization of Magnetic Field Intensity - Zhuang, Lin (Sci Rep, 2015)
Hydrophilic Fe(3)O(4) nanoparticles with controllable size and shape have been fabricated using a facile solvothermal approach followed by surface modification with polyacrylic acid (PAA). The nanoparticles form one-dimension photonic crystal structure under external magnetic field ranging from 29.6 to 459 G. The reflection peaks of formed photonic crystals cover the entire visible spectrum, which indicates a good magnetochromatic property and prospect of wide applications. The size and shape of Fe(3)O(4) nanoparticles are controlled by changing the ratio between ethylene glycol and diethylene glycol. In the process of surface modification, PAA synthesized by free radical polymerization was chemisorbed onto the surface of Fe(3)O(4) particles with the aid of Fe(3+) cations, which renders the particles well dispersed in aqueous solution with high thermo-stability. The Fe(3)O(4) particles exhibit ferrimagnetism with a high saturation magnetization value of 88.0 emu/g. Both the high magnetization and the wide reflection spectrum under magnetic field make the magnetochromatic nanoparticles a promising material for visualization of the distribution of magnetic field intensity on microfluidic chips.